1992
DOI: 10.1177/000992289203101004
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Invasive Group A Streptococcal Disease Among Young Children

Abstract: Eight cases of invasive group A streptococcal disease in young children were reported over a three-month period, February to April 1990. The spectrum of clinical disease included: pneumonia with bacteremia (two patients), osteomyelitis/septic arthritis (three patients), epiglottitis/supraglottitis (two patients), and sepsis without a focus (one patient). Three cases followed chicken pox. Three children were in shock at the time of presentation, including one child who had a toxic shock-like appearance. Only fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Our second study of hospitalised patients with invasive GAS infection revealed that bacteraemic cases in children were outnumbered at least two-or three-fold by those who were not proved bacteraemic. The spectrum of clinical conditions associated with invasive GAS in childhood was wide (see Table 3) and generally resembled those reported by others [1,[13][14][15][16][17][18]. Taken together, the range of possible manifestations is very similar to that seen in adults, although certain clinical forms such as varicella-or pharyngitis-associated infection, bone and joint infections and abscess may predominate.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Our second study of hospitalised patients with invasive GAS infection revealed that bacteraemic cases in children were outnumbered at least two-or three-fold by those who were not proved bacteraemic. The spectrum of clinical conditions associated with invasive GAS in childhood was wide (see Table 3) and generally resembled those reported by others [1,[13][14][15][16][17][18]. Taken together, the range of possible manifestations is very similar to that seen in adults, although certain clinical forms such as varicella-or pharyngitis-associated infection, bone and joint infections and abscess may predominate.…”
Section: Discussionsupporting
confidence: 77%
“…1) where the illness was modest and fleeting, resembling other forms of childhood doccult bacteraemiaT [26]. We saw no instances of toxic shock syndrome, necrotising soft tissue infection or pneumonia in children, although these forms have been reported by others [1,2,[5][6][7]11,14,16,18,20]. Only one in our series of 24 cases (4%) proved fatal (a 5-month-old diabetic child with very rapid clinical course), a much lower rate than that seen in the adults, but others have reported fatal infections with pneumonia, overwhelming sepsis, necrotising fasciitis and toxic shock syndrome in children [2,7,[10][11][12]14,17,18].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Severe invasive GAS infections of skin and soft tissues, such as myositis (muscle), cellulitis (dermis), and necrotizing fasciitis (subcutaneous tissue and fascia), can sometimes become life threatening (37,59). Streptococcal toxic shock syndrome, a soft-tissue infection characterized by shock, bacteremia, multiorgan failure, and a 30% mortality rate, has also been reported with increasing frequency in recent years (24,37,59,60). In some cases, GAS infections can lead to serious nonsuppurative sequelae such as rheumatic fever, acute glomerulonephritis, and rheumatic heart disease.…”
mentioning
confidence: 99%